Evaluación del proceso de elaboración de yogurt mediante la normativa arcsa 067 – 2015 de sanidad en alimentos procesados. - Guilcamaigua Flores, Elvia Susana (2019)
The purpose of this research work is to evaluate the process of making yogurt through the application of the ARCSA 067-2015 standard for processed foods in the FINO dairy company with the intention of improving the safety of production processes by previously carrying out the verification of the initial state of the company to later propose an improvement proposal taking into consideration the study as a field investigation that applies techniques such as direct observation, interview and documentary review to examine the food safety that allows to determine the compliance percentage of established parameters, being in this case, 62% compliance, 30.7% non-compliance and 6.6% does not apply to the company and these results allowed to identify operational problems for each stage of the process evidencing, the absence of POE and POES procedures that allow the control and monitoring of the processes in the plant so it is necessary to develop a manual BPM to improve the sanitary characteristics of yogurt by controlling cross contamination from the raw material (milk) to the finished product (yogurt) because the study It presents particularities that it seeks to control through the application of preventive and corrective measures throughout the process, concluding with this that the initial diagnosis of the company facilitates the evaluation of the different processes allowing to guarantee the elaboration of the yogurt through the control of the critical points and substances foreign to the product that will guarantee the guarantee and quality.